A hybrid positioning approach based on mechanical calculus model and grid simulation for drifting debris. (October 2016) - He, Yu-Ling; Wang, Wei-Kang; Zhang, Zhi-Qiu; Xu, Da
Abstract: This paper proposes an approach to position the drifting aircraft debris after a crash accident based on a hybrid model, which includes a mechanical calculus part and an advanced ocean model part. The most probable crash area is firstly established via mechanical calculus analysis on the normal forced landing process and the abnormal crashing process. Then the numerical simulation is taken to calculate the drifting process of the debris. A simulation approach based on the grid-measurement and the improved ocean model is used to predict the most possible domain of the drifting debris in the several following days. The impact of using the advanced ocean model on positioning the drifting debris is studied, on which the idealized current flow is used but the effect of winds is ignored. The case study of MH370 and the sensitivity analysis indicate the validity of the model. The proposed work enables further research on quick positioning of drifting debris after an aircraft crash. Highlights: We combine the mechanical calculus model with the advanced ocean model based grid simulation, to position the drifting debris. The proposed work is able to quickly calculate the most likely debris domain with a qualified precision. We have also carried out the case study of MH370, verifying that the proposed method is effective.